BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA UNTUK MENINGKATKAN KOHESIVITAS KELOMPOK (Studi Deskriptif kepada Siswa SMP PGII 2 Bandung Tahun Ajaran 2020/2021 dan Guru Bimbingan dan Konseling) - Rinrin Reza Lispandi, - (2022)
Group cohesion is a developmental task that contributes positively in supporting the development of the individual's personal, social, learning, and career fields. In general, the purpose of this research is to describe the cohesiveness of SMP PGII 2 students in Bandung in 2020/2021 Academic Year. The approach used is a quantitative approach with descriptive methods and cross sectional survey design research design. The research participants consisted of a sample of 377 class VII, VIII, and IX students. Data analysis techniques using the Rasch Model. The research findings show: (1) the tendency of group cohesiveness is in the low category, (2) the tendency of group cohesiveness of empathy cohesion components is in the very low category, (3) the implications of the formulation of group guidance programs with sociodrama techniques to improve group cohesiveness. Research recommendations are addressed to schools, counseling teachers, and further researchers.